The Development Of A Learning Management Model To Promote The Productivity Competencies Related To Citizenship, Culture, And Daily Life In Society For 2nd-Year High School Students At Phayakphum Wittayakhan School - Sirikit, Sutasinee (Mahachula Academic Journal, 2025)
The objectives of this research are (1) to study the basic information and synthesize the components of the learning management system to promote productivity competencies in civic duties, culture, and social living for second-year high school students, (2) to develop the learning management system to promote productivity competencies in civic duties, culture, and social living for second-year high school students, (3) to study the satisfaction with the use of the learning management system to promote productivity competencies in civic duties, culture, and social living for second-year high school students. This research employs a mixed-methods approach using an exploratory sequential design, starting with qualitative research and followed by quantitative research. The instruments used in the research included interviews with five key informants selected through purposive sampling. The experimental group consisted of 20 second-year high school students, obtained through purposive selection. Research findings: (1) Basic information on the learning management model for productivity in civic duties, culture, and social living includes: 1) Learning management conditions, 2) Guidelines or steps for organizing learning activities, 3) The teacher’s learning management model, 4) The learning atmosphere, and 5) The learners’ knowledge competencies., The synthesis of the components of the learning management model to promote productivity in civic duties, culture, and social living reveals that the learning management model consists of five components: 1) Principles, 2) Objectives, 3) Content related to civic duties, culture, and social living, 4) Learning management processes, and 5) Measurement and evaluation., The synthesis of the principles of the learning management model from theories, principles, and concepts, being the basis for developing the learning management model to promote productivity in civic duties, culture, and social living, shows that the principles of the learning management model focus on the learners’ learning processes. Learners independently research and seek knowledge through interaction with the environment, emphasizing practice and real-life application. Learners create knowledge themselves and apply it to develop productive ideas into works or projects independently using media and technology. (2) The development of a learning management system to promote productivity competencies in civic duties, culture, and social living found that the post-trial scores ( = 57.85, S.D. = 1.98) were significantly higher than the pre-trial scores ( = 34.75, S.D. = 3.57) at the 0.05 statistical significance level. (3) A study on the satisfaction of using a learning management model to promote the productivity competencies related to citizenship, culture, and daily life in society found that, overall, the average score was 4.34, which falls within the high range according to the established criteria.